Experiencia de vida pedagógica y de gestión de Luis Humberto Rodríguez Carvajal en la danza folclórica como eje transformador de vida en los estudiantes de las escuelas de formación del municipio de Facatativá. (2021)
This research relates my experience lived from the pedagogical and management field in the processes of growth in folk dance as a transforming axis of life in the students of the training schools of the municipality of Facatativá; understood in the years 2006 to 2019 through qualitative methodology, with a narrative writing applying as a data collection tool the interview with students, instructors and secretaries of culture who were part of the process. With the compilation of this experience, I seek to be a reference point for the trainers in folk dance to direct this language of art to the sensitization of society and find that this practice influences the lives of those who participate and the environment that surrounds them.